Stability, therrno-physical properties, and electrical conductivity of graphene oxide-deionized water/ethylene glycol based nanofluid - Ijam, A.; Saidur, R.; Ganesan, P.; Golsheikh, A.M. (Elsevier, 2015)
Stability, thermal conductivity, viscosity, specific heat, density and electrical conductivity of graphene oxide nanosheets-(60:40) deionized water/ethylene glycol (GONs-DW/EG) were experimentally examined. The stability of the nanofluids is examined with sedimentation time. Experiments were carried out with a weight fraction of (0.01-0.10) and different temperatures. Nanofluids were found to be stable for more than 2 months. The thermal conductivity is improved by 6.67-10.47 at a weight fraction of 0.10 and temperature of (25-45) degrees C. The nanofluids showed a shear thinning behavior at low shear rate; however, it behaved in Newtonian manner with higher shear rate. The viscosity of 0.10 wt. GONs-DW/EG nanofluid is increased by 35 compared to the base fluid at a temperature of 20 degrees C. However, it decreased by 48 with increasing the temperature from 20 to 60 degrees C for the same loading of GONs. The specific heat of the GONs-DW/EG nanofluid increased by 3.59-5.28 with a weight fraction of 0.05 and decreased by 9.05-8.215 with a weight fraction of 0.10 with temperature range of 20-60 degrees C. The density of the GONs-DW/EG nanofluid at weight fraction of 0.10 is decreased by 1.134-1 with temperature of 25-45 degrees C. An improvement in electrical conductivity of about 1664 is achieved at a weight fraction of 0.10 and temperature of 25 degrees C. Correlations were developed for predicting thermo-physical properties and electrical conductivity of the nanofluids based on the experimental data. (C) 2015 Elsevier Ltd, All rights reserved.